Developing mathematics learning set for special-needs junior high school student oriented to learning interest and achievement - Ai Sadidah; Ariyadi Wijaya (Jurnal Riset Pendidikan Matematika, 2016)
This study aims to produce a mathematics learning set for special-needs students (mathematical learning disability and mathematically gifted) of Junior High School Grade VIII Second Semester oriented to learning interests and achievement which is valid, practical, and effective. This study was a research and development study using the Four-D development model consisting of four stages: (1) define, (2) design, (3) develop, and (4) disseminate. The quality of learning set consisting of the following three criterions: (1) validity, (2) practicality, and (3) effectiveness.  The data analysis technique used in this study is a descriptive quantitative analysis. The research produced learning set consisting of lesson plans and student worksheets. The result of the research shows that: (1) the learning set fulfill the valid criteria base on experts’ appraisal; (2) the learning set fulfill the practical criterion base on teacher’s and students’ questionnaire, and observation of learning implementation; (3) the learning set fulfill the effectiveness criterion base on learning interest and achievement.